#TITLE_ALTERNATIVE# - FIRMAN BASKARA (NIM : 10213039), RAKA
The objective of this study is to analysis some neutronic aspect about direct recycling nuclear spent fuel in Westinghouse AP1000 nuclear reactor and to analysis some neutronic aspect about Thorium based AP1000 nuclear reactor using ThO2-UO2 and ThO2-PuO2 fuel. In first analysis, conducted recycling scenario is to recycle spent AP1000 fuel directly in AP1000 nuclear reactor in multi cycle concept. As for the second analysis of Thorium based AP1000 reactor, first ThO2-UO2 fuel is used with variation of enriched Uranium-235 and variation of the amount of ThO2 fuel. Secondly ThO2-PuO2 fuel cycle is used with Plutonium isotopes is taken from reactor grade Plutonium of PWR and then variation of the amount of Plutonium fuel that can be used for reactor in critical condition. Neutronic calculations were performed using the SRAC 2006 code system with the JENDL 4.0 nuclear data base. The result obtained from this study are relation of the percentage of spent fuel used with the number of cycles that can be done, the value effective multiplication factor, convertion ratio, atomic density of various fissile materials, neutron spectrum and reactor core power distribution for each analysis. For AP1000 reactor using ThO2-UO2 fuel, the critical condition can be achieved with a minimum percentage of ThO2 fuel is 1.5% and enrichment of UO2 is 4.45%. While for the ThO2-PuO2 fuel, the critical condition can be achieved when the minimum percentage of PuO2 is 22.5%. The convertion ratio for ThO2-UO2 fuel tends to increase, while for ThO2-PuO2 fuel tends to decrease. Neutron spectrum result shows that for both fuel cycles is predominant at fast energy neutron region.